Rancang Bangun Aplikasi Penapisan Calon Akseptor KB Berbasis Android “Tapis Yuk” - Astri Nurdiana (EMBRIO: Jurnal Kebidanan, 2020)
Midwives hold an essential role in providing family planning services, therefore it has to be appropriate and in accordance with the condition of prospective family planning acceptors. Every contraception service is needs to begin by family planning screening of acceptors, selecting the right and appropriate type of contraception could affect the women’s welfare and health in the future. The smartphones use is currently grow rapidly, as evidenced by the infographic of Indonesian smartphone users in 2019 reaching 355.5 million. In Indonesia, smartphones with the Android operating system are the largest market for use compared to other smartphone operating systems. The combination of the family planning service needs along with technology developments led to the idea of ​​creating an Android-based family planning contraception screening application called "Tapis Yuk". This research is an application design and building, that carried out in June-October 2020. The results obtained 1 android-based application that can be used as a medium for screening prospective family planning acceptors, the application can be used by midwives or other health workers.